Prefixes in Tagulandang Language - Rumorong, Estevin Melinda; Liando, Nihta V. F; Rorimpandey, Rinny (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
One element of culture is language. Wardaugh (1986:1) states that language is a system of communication in society. The science that studies language is linguistics. That the writer is interested in conductin g research on the Tagulandang language, especially prefixes. Prefixes are affixes that are attached in front of the basic form (basic words), prefixes are also called initial affixes (Sulchan, 1988:58). Prefix is ​​an affix that is added in front of the base form (Chaer 1994:178). This study does not cover all about prefixes, but it is focused on the form, functions, and meaning of prefixes mu-, nu-, and ni-. In conducting this research, the writer used qualitative approach by implementing the descriptive method. It is base on the empirical phenomena found on the speaker of the language. Data collection was carried out through direct interview and the author was also an informant. This reseach the interviews were guided by a list of Indonesian verbs and sentences, which contained prefixes and were then translated into Tagulandang. the data have collected are interpreted or conclude based on their form and function as the finding of the study. Concering the prefixes in Tagulandang language, it was taken three forms prefixes in Tagulandang language that possess the tenses.